Promoting skin‐to‐skin care for low birthweight babies: findings from the Ghana Newhints cluster‐randomised trial. Issue 8 (3rd June 2013) - Vesel, Linda; ten Asbroek, Augustinus H.A.; Manu, Alexander; Soremekun, Seyi; Tawiah Agyemang, Charlotte; Okyere, Eunice; Owusu‐Agyei, Seth; Hill, Zelee; Kirkwood, Betty R
Abstract Objective To evaluate whether the Newhints home visits intervention increased the adoption of skin‐to‐skin care (SSC), in particular, among low birthweight (LBW) (<2.5 kg) babies. Methods A cluster‐randomised trial, with 49 Newhints zones and 49 control zones, was conducted in seven districts in the Brong Ahafo Region, Ghana. It included all live births between November 2008 and December 2009. In Newhints zones, existing community‐based surveillance volunteers were trained to conduct home visits during which they weighed babies and counselled mothers of LBW babies on SSC. Performance of any SSC and SSC for more than 2 h was evaluated. Results Of 15, 615 live births, 68.5% had recorded birthweights; 10.1% were LBW. Any SSC was 19.4% higher among babies in Newhints vs. control zones (risk ratio, RR: 1.81; 95% confidence interval, CI: 1.40–2.35). Performance of SSC for more than 2 h was, however, low, at only 7.5%, although more than double compared with control zones (RR: 2.72; 95% CI: 1.80–4.10). LBW babies visited and weighed by a volunteer were more likely to receive SSC (PAny = 0.005; P > 2 h = 0.021), greater for LBW babies, particularly for more than 2 h of SSC (Pinteraction = 0.050). Conclusion Newhints successfully promoted the uptake of SSC in rural Ghana. Although findings are encouraging, promotion in rural community settings in sub‐Saharan Africa is challenging. Lessons learned can help shape SSC promotion in efforts to increase adoption and save newborn lives.